Method for preparing silicon composite oxide for negative electrode active material, negative electrode for secondary battery, and lithium secondary battery comprising same

By using a multi-layer structure negative electrode active material layer containing silicon composite oxide and carbon coating, the problem of damage to the negative electrode active material of lithium secondary battery during repeated charging and discharge is solved, and the power characteristics and stability of the battery are improved .

CN119447159APending Publication Date: 2025-02-14SK ON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410974453.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-31
Filing Date
2024-07-19
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The negative electrode active substances of existing lithium secondary batteries are prone to mechanical and chemical damage during repeated charging and discharging, resulting in a decrease in power characteristics and stability.

Method used

A silicon composite oxide containing a metal is used as the negative electrode active material, and a carbon coating is formed on its surface. By adjusting the specific surface area and crystal size of the silicon composite oxide, a multi-layer structure of the negative electrode active material layer is formed.

Benefits of technology

It improves the conductivity and charging capacity of lithium secondary batteries, enhances the stability and life characteristics of the negative electrode, and is suitable for green technology fields such as electric vehicles and battery charging stations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447159A_ABST
    Figure CN119447159A_ABST
Patent Text Reader

Abstract

A negative electrode for a secondary battery according to an exemplary embodiment may include: a negative electrode current collector; a first negative electrode active material layer that is provided on at least one surface of the negative electrode current collector and contains a first negative electrode active material containing a first silicon composite oxide; and a second negative electrode active material layer that is provided on the first negative electrode active material layer and contains a second negative electrode active material containing a second silicon composite oxide. The first silicon composite oxide and the second silicon composite oxide may each include a metal, and the BET specific surface area of the first silicon composite oxide and the second silicon composite oxide may be 2.0-6.5 m2 / g. Therefore, the charging / discharging capacity of the negative electrode can be increased while the stability of the negative electrode can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a silicon composite oxide used as a negative electrode active material, a negative electrode for a secondary battery and a lithium secondary battery comprising the negative electrode. Background Art

[0002] Secondary batteries are batteries that can be repeatedly charged and discharged. With the development of the information communication and display industries, secondary batteries are widely used as power sources for portable electronic communication devices such as camcorders, mobile phones, and notebook computers. In addition, in recent years, battery packs including secondary batteries are being developed and used as power sources for environmentally friendly vehicles such as electric vehicles and hybrid vehicles.

[0003] Examples of secondary batteries include lithium secondary batteries, nickel-cadmium batteries, and nickel-metal hydride batteries. Among them, lithium secondary batteries have high operating voltage and energy density per unit weight, and are advantageous in terms of charging speed and light weight, and therefore are being actively developed and used.

[0004] For example, a secondary battery may include: an electrode assembly including a positive electrode, a negative electrode and a separation membrane (diaphragm); and an electrolyte impregnated with the electrode assembly. The secondary battery may also include an outer packaging material such as a soft pack type outer packaging material that accommodates the electrode assembly and the electrolyte.

[0005] As the negative electrode active material contained in the negative electrode, a carbon-based active material and a silicon-based active material can be used. The silicon-based active material can provide a high capacity. However, in the case of repeated charge / discharge, the silicon-based active material may be susceptible to mechanical damage such as cracks of particles and chemical damage. Summary of the invention

[0006] 1. Technical issues to be resolved

[0007] An object of the present invention is to provide a negative electrode for a secondary battery having improved power characteristics and initial efficiency.

[0008] An object of the present invention is to provide a lithium secondary battery including a negative electrode for a secondary battery having improved power characteristics and initial efficiency.

[0009] An object of the present invention is to provide a method for producing a silicon composite oxide contained in a negative electrode for a secondary battery.

[0010] (II) Technical solution

[0011] A negative electrode for a secondary battery according to an exemplary embodiment may include: a negative electrode current collector; a first negative electrode active material layer, the first negative electrode active material layer is disposed on at least one side of the negative electrode current collector and includes a first negative electrode active material containing a first silicon composite oxide; and a second negative electrode active material layer, the second negative electrode active material layer is disposed on the first negative electrode active material layer and includes a second negative electrode active material containing a second silicon composite oxide. The first silicon composite oxide and the second silicon composite oxide may each contain a metal, and the BET specific surface area of ​​the first silicon composite oxide and the second silicon composite oxide may be 2.0-6.5 m 2 / g.

[0012] In some embodiments, the metal may include magnesium.

[0013] In some embodiments, a carbon coating may be formed on the surface of each of the first silicon composite oxide and the second silicon composite oxide, and may include SiO doped with magnesium. x (0 <x<2)。

[0014] In some embodiments, the first silicon composite oxide and the second silicon composite oxide may each include 5.0-10.0 wt % of a metal.

[0015] In some embodiments, the sum of the weight of the first silicon composite oxide and the second silicon composite oxide may be 10-20 wt % in the total weight of the first negative electrode active material layer and the second negative electrode active material layer.

[0016] In some embodiments, a content of the first silicon composite oxide included in the first negative electrode active material layer may be less than a content of the second silicon composite oxide included in the second negative electrode active material layer.

[0017] In some embodiments, the content of the first silicon composite oxide may be 2-10 wt % in the total weight of the first negative electrode active material layer.

[0018] In some embodiments, the content of the second silicon composite oxide may be 18-30 wt % in the total weight of the second negative electrode active material layer.

[0019] In some embodiments, a crystal size of the (220) plane defined by the following Formula 1 of each of the first silicon composite oxide and the second silicon composite oxide may be 3.5-10 nm.

[0020] [Formula 1]

[0021]

[0022] In formula 1, L 220 is the crystal size of the (220) plane (nm), K is the shape factor, λ is the X-ray wavelength (nm), β 220 is the half maximum width (radian (rad)) of the peak of the (220) plane analyzed by XRD, and θ is the diffraction angle (radian).

[0023] In some embodiments, the BET specific surface areas of the first silicon composite oxide and the second silicon composite oxide may be 2.5-6.0 m 2 / g.

[0024] A lithium secondary battery according to an exemplary embodiment may include: the above-described negative electrode for a secondary battery; and a positive electrode disposed opposite to the negative electrode.

[0025] In the preparation method of the silicon composite oxide for negative electrode active material according to the exemplary embodiment, a mixed gas of silicon (Si), silicon dioxide (SiO2) and metal can be reacted to form a primary silicon composite oxide. A carbon source with a pyrolysis temperature of 500-700° C. can be used to form a carbon coating on the surface of the primary silicon composite oxide.

[0026] In some embodiments, the metal may include magnesium.

[0027] In some embodiments, the carbon source may include at least one of ethylene and acetylene.

[0028] (III) Beneficial effects

[0029] The negative electrode for a secondary battery according to an exemplary embodiment of the present invention provides high conductivity, and a lithium secondary battery including the negative electrode has an improved charging capacity. The negative electrode active material layer of the negative electrode can be formed into a multilayer structure, and as the charging capacity of the lithium secondary battery increases, the stability can also be improved.

[0030] According to the method for preparing a silicon composite oxide for a negative electrode active material according to an exemplary embodiment of the present invention, carbon can be uniformly coated on the surface of the silicon composite oxide. Therefore, the curvature of the surface of the silicon composite oxide can be reduced, thereby improving the stability of the negative electrode containing the silicon composite oxide.

[0031] The negative electrode of the present invention and the lithium secondary battery including the negative electrode can be widely used in electric vehicles, battery charging stations, other green technology fields such as solar power generation and wind power generation using batteries. The negative electrode of the present invention and the lithium secondary battery including the negative electrode can be used in eco-friendly electric vehicles, hybrid vehicles, etc. to prevent climate change by suppressing air pollution and greenhouse gas emissions. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 and Figure 2 is a schematic cross-sectional view showing a negative electrode for a secondary battery according to an exemplary embodiment.

[0033] Figure 3 and Figure 4 1 and 2 are respectively a schematic plan view and a schematic cross-sectional view showing a lithium secondary battery according to an exemplary embodiment.

[0034] Figure 5 is a schematic flowchart for explaining a method for preparing a silicon composite oxide for a negative electrode active material according to an exemplary embodiment. DETAILED DESCRIPTION

[0035] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings and embodiments. However, these are merely exemplary embodiments, and the present invention is not limited to the specific embodiments exemplarily described.

[0036] The terms “bottom surface”, “upper surface”, etc. used in the present invention are used in a relative sense to distinguish the positions of components, rather than to specify absolute positions.

[0037] <Negative electrode for secondary battery>

[0038] Figure 1 and Figure 2 is a schematic cross-sectional view showing a negative electrode for a secondary battery according to an exemplary embodiment.

[0039] Reference Figure 1 The negative electrode 130 may include a negative electrode active material layer 120 disposed on at least one side of a negative electrode collector 125 .

[0040] According to an exemplary embodiment, the negative active material layer 120 may have a multi-layer structure including a first negative active material layer 122 and a second negative active material layer 124 .

[0041] The negative electrode current collector 125 may include, for example, copper foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, a polymer substrate coated with a conductive metal, or the like.

[0042] The negative active material layer 120 may be coated on at least one of the upper surface and the bottom surface of the negative current collector 125. The negative active material layer 120 may directly contact the surface of the negative current collector 125.

[0043] According to an exemplary embodiment, the first negative active material layer 122 may be directly formed on the surface of the negative current collector 125. The second negative active material layer 124 may be directly formed on the surface of the first negative active material layer 122.

[0044] The first negative electrode active material layer 122 may include a first negative electrode active material including a first silicon composite oxide, and the second negative electrode active material layer 124 may include a second negative electrode active material including a second silicon composite oxide.

[0045] The term "silicon composite oxide" used in the present invention may refer to a compound or material in which silicon oxide and an element other than silicon and oxygen are mixed or integrated.

[0046] According to an exemplary embodiment, the first silicon composite oxide and the second silicon composite oxide may each contain a metal. For example, the metal may contain magnesium (Mg), aluminum (Al), zinc (Zn), bismuth (Bi), cadmium (Cd), lead (Pb), zirconium (Zr), tin (Sn), gallium (Ga), indium (In), yttrium (Y), cesium (Cs), niobium (Nb), etc. Therefore, the initial capacity efficiency of the secondary battery containing the silicon composite oxide can be improved.

[0047] In some embodiments, the first silicon composite oxide and the second silicon composite oxide may include a carbon coating on their respective surfaces. For example, the carbon coating may be coated using at least one of ethylene and acetylene as a carbon source. Therefore, the life stability of the silicon composite oxide may be improved.

[0048] Silicon oxide can react with relatively more Li ions. Therefore, by using silicon oxide as a negative electrode active material, the capacity of the secondary battery can be increased. However, when silicon oxide reacts with Li ions, the volume expansion of the negative electrode active material increases, and the life characteristics and stability of the negative electrode may be reduced. In addition, silicon oxide may have a relatively low conductivity.

[0049] However, according to an exemplary embodiment, a silicon composite oxide containing a metal can be used as a negative electrode active material. Therefore, the conductivity of the silicon composite oxide and the negative electrode containing the silicon composite oxide can be improved. In addition, a carbon coating can be formed on the silicon composite oxide. Therefore, the life stability of the silicon composite oxide can be improved.

[0050] In some embodiments, the metal may include magnesium and may further improve the conductivity of the silicon composite oxide.

[0051] In some embodiments, in the total weight of the first silicon composite oxide and the second silicon composite oxide, the content of the metal (e.g., magnesium) contained in the first silicon composite oxide and the second silicon composite oxide may be 5.0 - 10.0 wt%, 7.0 - 9.0 wt%, 7.0 - 8.0 wt%, or 7.7 - 8.0 wt%, respectively. Within the above metal (e.g., magnesium) content range, the reduction of the life characteristics of the silicon composite oxide can be inhibited, and the conductivity of the silicon composite oxide can be improved by the metal (e.g., magnesium). Therefore, the initial capacity efficiency can be improved.

[0052] In some embodiments, a carbon coating may be formed on the surface of each of the first silicon composite oxide and the second silicon composite oxide, and each of the first silicon composite oxide and the second silicon composite oxide may be doped with magnesium. For example, each of the first silicon composite oxide and the second silicon composite oxide may contain SiO x (0 < x < 2).

[0053] In one embodiment, each of the first silicon composite oxide and the second silicon composite oxide may contain SiO doped with magnesium x (0 < x < 2). In addition, a carbon coating may be formed on the surface of SiO doped with magnesium x (0 < x < 2).

[0054] Therefore, the energy density can be increased by the silicon oxide (e.g., SiO x (0 < x < 2)), and the conductivity can be increased by the magnesium doped in the silicon oxide. Therefore, the initial capacity efficiency and long-term life characteristics of the first silicon composite oxide and the second silicon composite oxide can be improved.

[0055] According to an exemplary embodiment, the first silicon composite oxide as the first negative electrode active material may be used together with a substance that allows lithium ions to be inserted and extracted. The second silicon composite oxide as the second negative electrode active material may be used together with a substance that allows lithium ions to be inserted and extracted.

[0056] The substance that allows lithium ions to be inserted and extracted may include, for example, carbon-based materials such as crystalline carbon, amorphous carbon, carbon composites, carbon fibers; lithium metal; lithium alloys; silicon (Si)-containing substances or tin (Sn)-containing substances, etc.

[0057] Examples of the amorphous carbon include hard carbon, soft carbon, coke, mesocarbon microbeads (MCMB), mesophase pitch-based carbon fiber (MPCF), and the like.

[0058] Examples of the crystalline carbon include graphite-based carbon such as natural graphite, artificial graphite, graphitized coke, graphitized MCMB, and graphitized MPCF.

[0059] The lithium metal may refer to a metal layer containing lithium. A protective layer for suppressing dendrite growth, etc. may be formed on the lithium metal. In one embodiment, a layer containing lithium metal deposited or coated on a negative electrode current collector may be used as a negative electrode active material layer. In one embodiment, a lithium thin film layer or lithium foil may also be used as a negative electrode active material layer.

[0060] Examples of the element contained in the lithium alloy include aluminum, zinc, bismuth, cadmium, antimony, silicon, lead, tin, gallium, and indium.

[0061] The silicon (Si)-containing material may include Si and a silicon-carbon composite.

[0062] In some embodiments, the sum of the weights of the first silicon composite oxide and the second silicon composite oxide in the total weight of the first negative electrode active material layer 122 and the second negative electrode active material layer 124 may be 10-20 wt %. Within the above weight range, the charge capacity of the secondary battery can be increased. In one embodiment, the sum of the weights of the first silicon composite oxide and the second silicon composite oxide in the total weight of the first negative electrode active material layer 122 and the second negative electrode active material layer 124 may be 11-17 wt %, 12-17 wt %, or 12-15 wt %. Within the above weight range, the charge capacity and stability of the secondary battery can be increased at the same time.

[0063] In some embodiments, the content of the first silicon composite oxide contained in the first negative electrode active material layer 122 on a weight basis may be less than the content of the second silicon composite oxide contained in the second negative electrode active material layer 124 on a weight basis. Therefore, the average content of the silicon composite oxide contained in the negative electrode active material layer 120 may be reduced, and the content of the silicon composite oxide in contact with the electrolyte may be increased. Therefore, the stability and charge capacity of the negative electrode 130 may be improved.

[0064] In some embodiments, the content of the first silicon composite oxide may be 2-10 wt % in the total weight of the first negative electrode active material layer 122. Within the above range, the content of the first silicon composite oxide included in the first negative electrode active material layer 122 may be reduced, thereby reducing the average content of the silicon composite oxide included in the negative electrode active material layer 120.

[0065] Therefore, the decrease in stability caused by the volume expansion of the negative electrode active material layer 120 is suppressed, thereby having improved stability. For example, the content of the first silicon composite oxide may be 3-8 wt %, 4-8 wt %, or 4-6 wt % in the total weight of the first negative electrode active material layer 122. Within the above content range, the stability caused by the volume expansion of the negative electrode active material layer 120 may be further improved.

[0066] In some embodiments, the content of the second silicon composite oxide may be 18-30 wt % of the total weight of the second negative electrode active material layer 124. Within the above range, the content of the second silicon composite oxide included in the second negative electrode active material layer 124 in direct contact with the electrolyte may be increased, thereby increasing the energy density of the negative electrode.

[0067] Therefore, the charging capacity of the secondary battery can be improved. In one embodiment, the content of the second silicon composite oxide can be 19-26 wt %, 20-26 wt % or 20-24 wt % in the total weight of the second negative electrode active material layer 124. Within the above range, the charging capacity of the lithium secondary battery can be further improved.

[0068] In some embodiments, the crystal size of the (220) plane of each of the first silicon composite oxide and the second silicon composite oxide defined by the following formula 1 may be 3.5-10.0 nm. Within the above crystal size range, aggregation and side reactions between silicon composite oxides caused by excessive reduction in the size of the silicon composite oxides can be prevented, thereby improving the life characteristics of the negative electrode. In addition, volume instability caused by excessive increase in the crystal size of the silicon composite oxide can be prevented, thereby improving the life characteristics.

[0069] In one embodiment, the crystal size of the (220) plane of the first silicon composite oxide and the second silicon composite oxide defined by the following formula 1 may be 5.0-9.0 nm, 5.0-7.0 nm or 6.0-7.0 nm. Within the above crystal size range, the life characteristics of the negative electrode can be further improved.

[0070] [Formula 1]

[0071]

[0072] In formula 1, L 220 represents the crystal size of the (220) plane (nm), K represents the shape factor, λ represents the X-ray wavelength (nm), β 220 represents the half maximum width (radian) of the peak of the (220) plane analyzed by XRD, and θ represents the diffraction angle (radian). The shape factor (K) may be, for example, 0.8 or 0.9.

[0073] According to an exemplary embodiment, the BET specific surface area of ​​each of the first silicon composite oxide and the second silicon composite oxide may be 2.0-6.5 m 2 When the BET specific surface area of ​​the first silicon composite oxide and the second silicon composite oxide is less than 2.0 m 2 / g, the reaction area is reduced, and thus the initial capacity efficiency may be reduced. In addition, when the BET specific surface area of ​​the first silicon composite oxide and the second silicon composite oxide exceeds 6.5 m 2 / g, the silicon composite oxide may react with the electrolyte solution, etc., causing a side reaction, thereby reducing the initial capacity efficiency. Therefore, by adjusting the BET specific surface area of ​​the first silicon composite oxide and the second silicon composite oxide to the above range, the initial efficiency of the secondary battery can be improved.

[0074] In some embodiments, the BET specific surface area of ​​each of the first silicon composite oxide and the second silicon composite oxide may be 2.0-6.4 m 2 / g or 2.5-6.4m 2 In one embodiment, the BET specific surface area of ​​the first silicon composite oxide and the second silicon composite oxide may be 2.5-6.0 m 2 / g or 2.5-4.0m 2 / g.

[0075] In the above specific surface area range, the contact area between the silicon composite oxide and lithium can be sufficiently increased, and the side reaction can be suppressed. Therefore, the initial efficiency of the secondary battery including the first silicon composite oxide and the second silicon composite oxide can be further improved.

[0076] The BET specific surface areas of the first silicon composite oxide and the second silicon composite oxide may be measured by a Brunauer-Emmett-Teller (BET) method.

[0077] According to an exemplary embodiment, the first negative electrode slurry may be prepared by dispersing the first negative electrode active material including the first silicon composite oxide in a solvent. The first negative electrode slurry may further include a binder, and may optionally further include a conductive material, a thickener, and the like.

[0078] According to an exemplary embodiment, the second negative electrode slurry may be prepared by dispersing the second negative electrode active material including the second silicon composite oxide in a solvent. The second negative electrode slurry may further include a binder, and may optionally further include a conductive material, a thickener, and the like.

[0079] According to an exemplary embodiment, the first negative active material layer 122 and the second negative active material layer 124 may be manufactured by coating the first negative electrode slurry and the second negative electrode slurry on the negative electrode collector 125 , followed by drying and rolling.

[0080] For example, the first negative electrode slurry may be coated on the negative electrode collector 125 and then the second negative electrode slurry may be coated on the first negative electrode slurry. For example, the first negative electrode slurry and the second negative electrode slurry may be coated on the negative electrode collector 125 together. Afterwards, the first negative electrode slurry coated on the negative electrode collector 125 and the second negative electrode slurry coated on the first negative electrode slurry may be dried together. Therefore, the first negative electrode active material layer 122 and the second negative electrode active material layer 124 may be sequentially stacked on the negative electrode collector 125.

[0081] As described above, the first negative electrode slurry and the second negative electrode slurry are applied together and then dried at the same time, so that the first negative electrode active material layer 122 and the second negative electrode active material layer 124 can be formed substantially at the same time.

[0082] In one embodiment, the first negative electrode active material layer 122 and the second negative electrode active material layer 124 may also be formed separately. For example, after the first negative electrode slurry is coated on the negative electrode current collector 125 and dried to form the first negative electrode active material layer 122, the second negative electrode slurry is coated on the first negative electrode active material layer 122 and dried to form the second negative electrode active material layer 124.

[0083] As non-limiting examples of the solvent used for the first negative electrode slurry and the second negative electrode slurry, water, pure water, deionized water, distilled water, ethanol, isopropyl alcohol, methanol, acetone, n-propyl alcohol, tert-butyl alcohol, and the like may be cited.

[0084] The adhesive may be a styrene-butadiene rubber (SBR)-based adhesive, carboxymethyl cellulose (CMC), a polyacrylic acid-based adhesive, a polyethylenedioxythiophene (PEDOT)-based adhesive, or the like.

[0085] The conductive material may be added to enhance the conductivity and / or mobility of lithium ions or electrons of the negative electrode active material layer 120. For example, the conductive material may include carbon-based conductive materials such as graphite, carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, vapor-grown carbon fiber (VGCF), carbon fiber, and / or metal-based conductive materials such as perovskite materials such as tin, tin oxide, titanium oxide, LaSrCoO3, and LaSrMnO3.

[0086] As the thickener, for example, carboxymethyl cellulose (CMC) can be used.

[0087] Reference Figure 2 , the negative electrode active material layer 120 may include a first negative electrode active material layer 122 and a second negative electrode active material layer 124, wherein the first negative electrode active material layer 122 is directly formed on both sides of the negative electrode collector 125, and the second negative electrode active material layer 124 is formed on the first negative electrode active material layer 122. For example, a two-layer structured negative electrode active material layer 120 may be provided on both sides of the negative electrode collector 125, wherein the negative electrode active material layer 120 includes a first negative electrode active material layer 122 and a second negative electrode active material layer 124 sequentially stacked from the surface of the negative electrode collector 125.

[0088] <Lithium Secondary Battery>

[0089] According to an exemplary embodiment, a lithium secondary battery may include the above-described negative electrode for a secondary battery.

[0090] Figure 3 and Figure 4 are respectively a schematic plan view and a schematic cross-sectional view showing a lithium secondary battery according to an exemplary embodiment. Figure 4 It is along Figure 3 A cross-sectional view taken along the thickness direction along the line II'.

[0091] Figure 3 and Figure 4 An exemplary structure is shown for the convenience of description, and the structure of the lithium secondary battery of the present invention is not limited to the structure of Figure 3 and Figure 4 The structure shown.

[0092] Reference Figure 3 and Figure 4 The lithium secondary battery may include a positive electrode 100 and a negative electrode 130, and may further include a separator 140 interposed between the positive electrode 100 and the negative electrode 130. The positive electrode 100 may include a positive active material layer 110 disposed on at least one side of a positive current collector 105.

[0093] The positive electrode current collector 105 may include stainless steel, nickel, aluminum, titanium, or alloys thereof. The positive electrode current collector 105 may also include aluminum or stainless steel surface-treated with carbon, nickel, titanium, or silver.

[0094] The positive electrode active material layer 110 may include a positive electrode active material. The positive electrode active material may include a compound that can reversibly intercalate and deintercalate lithium ions.

[0095] According to an exemplary embodiment, the positive electrode active material may include lithium-nickel metal oxide. The lithium-nickel metal oxide may further include at least one of cobalt (Co), manganese (Mn), and aluminum (Al).

[0096] In some embodiments, the positive active material or the lithium-nickel metal oxide may include a layered structure or a crystal structure represented by the following Chemical Formula 1.

[0097] [Chemical formula 1]

[0098] Li x Ni a M b O 2+z

[0099] In Chemical Formula 1, 0.9≤x≤1.2, 0.5≤a≤0.99, 0.01≤b≤0.5, and -0.5≤z≤0.1 may be satisfied. As described above, M may include Co, Mn, and / or Al.

[0100] The chemical structure represented by Chemical Formula 1 represents the bonding relationship contained in the layered structure or crystal structure of the positive active material, and does not exclude other additional elements. For example, M may include Co and / or Mn, and Co and Mn may be provided together with Ni as the main active element of the positive active material. Chemical Formula 1 is provided to represent the bonding relationship of the main active elements, and it should be understood that Chemical Formula 1 is a formula including the introduction and substitution of additional elements.

[0101] In one embodiment, in addition to the main active element, an auxiliary element for enhancing the chemical stability of the positive electrode active material or the layered structure / crystal structure may be further included. The auxiliary element may be mixed together into the layered structure / crystal structure to form a bond, and it should be understood that this case is also included in the chemical structure represented by Chemical Formula 1.

[0102] The auxiliary element may include, for example, at least one of Na, Mg, Ca, Y, Ti, Hf, V, Nb, Ta, Cr, Mo, W, Fe, Cu, Ag, Zn, B, Al, Ga, C, Si, Sn, Sr, Ba, Ra, P, or Zr. The auxiliary element may function as an auxiliary active element that contributes to the capacity / power activity of the positive electrode active material together with Co or Mn, such as Al.

[0103] For example, the positive active material or the lithium-nickel metal oxide may include a layered structure or a crystal structure represented by the following Chemical Formula 1-1.

[0104] [Chemical formula 1-1]

[0105] Li x Ni a M1 b1 M2 b2 O 2+z

[0106] In Chemical Formula 1-1, M1 may include Co, Mn and / or Al. M2 may include the auxiliary elements described above. In Chemical Formula 1-1, 0.9≤x≤1.2, 0.5≤a≤0.99, 0.01≤b1+b2≤0.5, and -0.5≤z≤0.1 may be selected.

[0107] The positive electrode active material may further include a coating element or a doping element. For example, an element substantially the same as or similar to the auxiliary element may be used as the coating element or the doping element. For example, one or a combination of two or more of the above elements may be used as the coating element or the doping element.

[0108] The coating element or the doping element may be present on the surface of the lithium-nickel metal oxide particle or permeate through the surface of the lithium-nickel metal oxide particle and be included in the bonding structure represented by the Chemical Formula 1 or the Chemical Formula 1-1.

[0109] The positive active material may include a nickel-cobalt-manganese (NCM)-based lithium oxide. In this case, the NCM-based lithium oxide having an increased nickel content may be used.

[0110] Ni can be provided as a transition metal related to the power and capacity of a lithium secondary battery. Therefore, as described above, by using a high-content (high-nickel (High-Ni)) composition for the positive electrode active material, a high-capacity positive electrode and a high-capacity lithium secondary battery can be provided.

[0111] However, as the Ni content increases, the long-term storage stability and life stability of the positive electrode or secondary battery may be relatively reduced, and the side reaction with the electrolyte may also increase. However, according to an exemplary embodiment, the conductivity can be maintained by including Co, while the life stability and capacity retention characteristics can be improved by Mn.

[0112] In some embodiments, the content of Ni in the NCM-based lithium oxide (e.g., the molar fraction of nickel in the total moles of nickel, cobalt and manganese) may be 0.8 or more, 0.85 or more, 0.87 or more, or 0.90 or more. In some embodiments, the content of Ni may be 0.85 to 0.99, 0.85 to 0.97, 0.85 to 0.95, 0.87 to 0.95, or 0.90 to 0.95. Within the above Ni content range, the capacity characteristics of the positive electrode and the lithium secondary battery may be improved.

[0113] For example, the positive electrode slurry may be prepared by dispersing the positive electrode active material in a solvent. The positive electrode 100 may be manufactured by coating the positive electrode slurry on the positive electrode collector 105, drying and rolling. The positive electrode slurry may further include a binder, and may optionally further include a conductive material, a thickener, and the like.

[0114] Non-limiting examples of the solvent used in the preparation of the positive electrode slurry include N-methyl-2-pyrrolidone (NMP), dimethylformamide, dimethylacetamide, N,N-dimethylaminopropylamine, ethylene oxide, tetrahydrofuran, and the like.

[0115] The binder may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (poly(vinylidene fluoride-co-hexafluoropropylene)), polyacrylonitrile, polymethylmethacrylate, acrylonitrile rubber (NBR), polybutadiene rubber (BR), styrene-butadiene rubber (SBR), etc. In one embodiment, a PVDF-based binder may be used as a positive electrode binder.

[0116] As the conductive material and thickener, the above-mentioned substances that can be used when manufacturing the negative electrode can be used.

[0117] The negative electrode 130 may include the above-mentioned negative electrode for a secondary battery.

[0118] In some embodiments, the separator 140 may be disposed between the positive electrode 100 and the negative electrode 130. Through the separator, a short circuit between the positive electrode 100 and the negative electrode 130 may be prevented, and the flow of ions may be maintained.

[0119] The separator 140 may include a porous polymer film or a porous non-woven fabric. The porous polymer film may include polyolefin-based polymers such as ethylene polymers, propylene polymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers. The porous non-woven fabric may include high-melting-point glass fibers, polyethylene terephthalate fibers, and the like.

[0120] The separator 140 may also include a ceramic-based material. For example, inorganic particles may be coated on or dispersed in the polymer film to improve heat resistance.

[0121] The separator 140 may have a single-layer or multi-layer structure including the above-mentioned polymer film and / or non-woven fabric.

[0122] According to an exemplary embodiment, the electrode assembly 150 may be formed by repeatedly disposing the positive electrode 100, the negative electrode 130, and the separator 140. In some embodiments, the electrode assembly 150 may have a jelly roll form formed by winding, stacking, or z-folding the separator 140.

[0123] In one embodiment, the electrode assembly 150 may have a jelly roll form formed by winding the positive electrode 100, the negative electrode 130, and the separator 140. In one embodiment, the electrode assembly 150 may have a jelly roll form in which the positive electrode 100 and the negative electrode 130 are notched in a space formed by repeatedly folding the separator 140 in a zigzag shape.

[0124] In one embodiment, the electrode assembly 150 may be formed by cutting or separating a positive electrode, a negative electrode, and a separator from each other, respectively, between each layer and repeatedly stacking.

[0125] For example, the tabs (positive tabs and negative tabs) may protrude from the positive current collector 105 and the negative current collector 125 and extend to one side of the case, respectively. The tabs may be fused to the one side of the case 160 and connected to the leads (positive lead 107 and negative lead 127) extending to the outside of the case 160 or exposed to the outside of the case 160.

[0126] For example, a pouch-type case, a prismatic case, a cylindrical case, a coin-shaped case, etc. may be used.

[0127] The electrode assembly is housed in the case 160 together with an electrolyte, thereby defining a lithium secondary battery. According to an exemplary embodiment, the electrolyte may use a non-aqueous electrolyte.

[0128] The non-aqueous electrolyte may include a lithium salt as an electrolyte and an organic solvent. The lithium salt may be, for example, Li + X - Represents, and as the anion of the lithium salt (X - ), we can exemplify F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CR2SO2)2N - wait.

[0129] The organic solvent may include an organic compound that has sufficient solubility for the lithium salt and additives and is not reactive in the battery.

[0130] The organic solvent may include, for example, at least one of a carbonate-based solvent, an ester-based solvent, an ether-based solvent, a ketone-based solvent, an alcohol-based solvent, and an aprotic solvent. As the organic solvent, for example, propylene carbonate (PC), ethylene carbonate (EC), butylene carbonate, diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propyl carbonate, ethyl propyl carbonate, dipropyl carbonate, vinylene carbonate, methyl acetate (MA), ethyl acetate (EA), n-propyl acetate (n-PA), 1,1-dimethylethyl acetate (DMEA), methyl propionate (MP), ethyl propionate (EP), fluoroethyl acetate (FEA), difluoroethyl acetate (DFEA), trifluoroethyl acetate (TFEA), dibutyl ether, tetraethylene glycol dimethyl ether (TEGDME), diethylene glycol dimethyl ether (DME), ether, DEGDME), dimethoxyethane, tetrahydrofuran (THF), 2-methyltetrahydrofuran, ethyl alcohol, isopropyl alcohol, dimethyl sulfoxide, acetonitrile, diethoxyethane, cyclopentane, γ-butyrolactone and propylene sulfite, etc. These can be used alone or in combination of two or more.

[0131] The non-aqueous electrolyte may further include an additive. The additive may include, for example, a cyclic carbonate-based compound, a fluorine-substituted carbonate-based compound, a sultone-based compound, a cyclic sulfate-based compound, a cyclic sulfite-based compound, a phosphate-based compound, and a borate-based compound.

[0132] The cyclic carbonate-based compound may include vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and the like.

[0133] The fluorine-substituted cyclic carbonate-based compound may include fluoroethylene carbonate (FEC) and the like.

[0134] The sultone-based compound may include 1,3-propane sultone, 1,3-propene sultone, 1,4-butane sultone, and the like.

[0135] The cyclic sulfate-based compound may include 1,2-ethylene sulfate, 1,2-propylene sulfate, and the like.

[0136] The cyclic sulfite-based compound may include ethylene sulfite, butylene sulfite, and the like.

[0137] The phosphate-based compound may include lithium difluoro bis-oxalato phosphate, lithium difluoro phosphate, and the like.

[0138] The borate-based compound may include lithium bis(oxalate) borate and the like.

[0139] <Method for preparing silicon composite oxide for negative electrode active material>

[0140] Figure 5 is a schematic flowchart for explaining a method for preparing a silicon composite oxide for a negative electrode active material according to an exemplary embodiment.

[0141] Reference Figure 5 , a mixed gas including silicon (Si), silicon dioxide (SiO 2 ), and metal may be formed (eg, process S10 ).

[0142] For example, the metal may include magnesium (Mg), aluminum (Al), zinc (Zn), bismuth (Bi), cadmium (Cd), lead (Pb), zirconium (Zr), tin (Sn), gallium (Ga), indium (In), yttrium (Y), cesium (Cs), niobium (Nb), etc. Therefore, since the silicon composite oxide may include a metal, the initial capacity efficiency may be improved.

[0143] In some embodiments, the metal may include magnesium. For example, the mixed gas may include silicon, silicon dioxide, and magnesium. Therefore, since the silicon composite oxide may include magnesium, the phase change phenomenon of the silicon composite oxide under high voltage may be prevented, thereby improving the initial capacity efficiency and long-term life characteristics.

[0144] In some embodiments, the content of the metal (e.g., magnesium) in the mixed gas may be 5.0-10.0 wt%, 7.0-9.0 wt%, 7.0-8.0 wt%, or 7.7-8.0 wt% on a weight basis. The content of the metal contained in the mixed gas may be substantially the same as the content of the metal contained in the first silicon composite oxide and the second silicon composite oxide.

[0145] For example, the metal content of the first silicon composite oxide and the second silicon composite oxide can be determined according to the metal content contained in the mixed gas. Within the above range, the lifetime characteristics of the silicon composite oxide can be suppressed from being reduced, while the conductivity can be improved by the metal (e.g., magnesium), and the initial capacity efficiency can be improved.

[0146] In some embodiments, the mixed gas can be formed by gasifying silicon powder, silicon dioxide powder and magnesium powder independently. For example, the silicon powder, silicon dioxide powder and magnesium powder can be heated and evaporated in separate reactors different from each other to gasify. The silicon powder, silicon dioxide powder and magnesium powder gasified in separate reactors can be injected into one reactor and mixed with each other. Therefore, the silicon powder, silicon dioxide powder and magnesium powder can be gasified independently and form a mixed gas.

[0147] In one embodiment, the silicon powder may be gasified at 2000-3300° C., 2200-3300° C., or 2300-3300° C. Within the above temperature range, the silicon powder may be sufficiently gasified.

[0148] In one embodiment, the silicon dioxide powder may be gasified at 1200-2300° C., 1500-2300° C., or 1800-2300° C. Within the above temperature range, the silicon dioxide powder may be sufficiently gasified.

[0149] In one embodiment, the magnesium powder may be gasified at 1000-1200° C., 1050-1200° C., or 1050-1150° C. Within the above temperature range, the magnesium powder may be fully gasified.

[0150] According to an exemplary embodiment, the mixed gas may be reacted to form a primary silicon composite oxide (eg, process S20 ).

[0151] In some embodiments, after the mixed gas is reacted, the reacted mixed gas can be cooled. For example, the reacted mixed gas can be cooled by a cooling substrate. The cooling substrate can include a cooling plate, a cooling fin, and a cooling tube. For example, the reacted mixed gas can be cooled to room temperature (e.g., 25° C.) by the substrate.

[0152] As the mixed gas is cooled, silicon clusters may be formed. A magnesium-silicon oxide composite formed according to the following reaction formula 1 may be phase-separated from the silicon clusters, thereby stably doping magnesium into silicon and silicon oxide.

[0153] [Reaction formula 1]

[0154] Si+SiO2+Mg→Mg-SiO x (0 <x<2)

[0155] In some embodiments, the reacted mixed gas may be cooled at a pressure of 5-100 Pa, 5-80 Pa, 5-50 Pa, or 10-50 Pa. Within the above pressure range, magnesium may be doped between silicon oxides without causing a side reaction between the gaseous silicon, the gaseous silicon oxide, and the gaseous magnesium.

[0156] According to an exemplary embodiment, the primary silicon composite oxide may be pulverized (eg, process S30 ).

[0157] In some embodiments, the primary silicon composite oxide can be pulverized by a high-pressure pulverizing device such as an air jet mill (Air Jet Mill). For example, the primary silicon composite oxide can be added to an air jet mill and pulverized by the vibration caused by the high turbulence (high turbulence) of high-speed air and the pressure fluctuation caused by high frequency (high frequency).

[0158] According to an exemplary embodiment, the silicon composite oxide for a negative active material may be prepared by forming a carbon coating layer on the surface of the primary silicon composite oxide using a carbon source (eg, process S40 ).

[0159] In an exemplary embodiment, the carbon coating layer may be formed by pyrolysis of the carbon source. The pyrolysis temperature of the carbon source may be 500-700°C.

[0160] When silicon in the silicon composite oxide is exposed to high temperature, a partial bifurcation reaction may be performed. For example, silicon dioxide and silicon may be partially separated from the silicon composite oxide at high temperature. Therefore, when the carbon coating of the primary silicon composite oxide is formed at high temperature, the conductivity of the silicon composite oxide may be reduced.

[0161] However, according to an embodiment of the present invention, a carbon source having a pyrolysis temperature of 700° C. or less is used, so that carbon can be coated on the surface of the primary silicon composite oxide at a relatively low temperature. Therefore, a partial disproportionation reaction of the primary silicon composite oxide can be suppressed, and a carbon coating can be formed on the surface of the primary silicon composite oxide.

[0162] Therefore, the irregularities or curvature of the silicon composite oxide can be reduced, and an excessive increase in the BET specific surface area of ​​the silicon composite oxide can be suppressed.

[0163] For example, when the pyrolysis temperature of the carbon source is lower than 500° C., the speed of forming the carbon coating on the primary silicon composite oxide may be reduced. Therefore, the carbon coating of the silicon composite oxide may be unevenly formed and the specific surface area may be excessively reduced.

[0164] Therefore, by using a carbon source having a pyrolysis temperature in the above range, the BET specific surface area (e.g., 2.0-6.5 m 2 / g).

[0165] In some embodiments, the pyrolysis temperature of the carbon source may be 500-600° C., 500° C. or higher and lower than 600° C., or 500-580° C. Therefore, disproportionation of the silicon composite oxide can be prevented, and a silicon composite oxide having a BET specific surface area within the above range and having a carbon coating layer can be formed.

[0166] In some embodiments, the carbon source may include ethylene or acetylene. The pyrolysis temperature of ethylene or acetylene may be within the above-mentioned pyrolysis temperature range. Therefore, carbon may be uniformly coated on the primary silicon composite oxide, and disproportionation of the silicon composite oxide may be prevented, and a silicon composite oxide having a BET specific surface area within the above-mentioned range may be formed.

[0167] In one embodiment, the carbon source may be ethylene. In this case, carbon may be more uniformly coated on the primary silicon composite oxide.

[0168] For example, the carbon coating may be formed by a chemical vapor deposition (CVD) process.

[0169] In some embodiments, the carbon coating can be formed by CVD at a temperature of 500-1000° C., 500-900° C., 500-800° C., or 500-700° C. Within the above temperature range, the above carbon source can be pyrolyzed and CVD can be performed, and the conductivity of the silicon composite oxide can be improved by preventing the disproportionation of the primary silicon composite oxide. In addition, when the negative electrode containing the silicon composite oxide is charged, a solid electrolyte interface (SEI) layer can be stably formed.

[0170] The embodiments of the present invention are further described below with reference to specific experimental examples. The embodiments and comparative examples included in the experimental examples are only used to illustrate the present invention and are not used to limit the claims. Various modifications and variations can be made to the embodiments within the scope of the present invention and the technical concept, which is obvious to those skilled in the art, and it is natural that such modifications and variations belong to the scope of the claims.

[0171] Examples and Comparative Examples

[0172] Example 1

[0173] 1) Preparation of silicon composite oxide

[0174] Silicon powder, silicon dioxide powder and magnesium powder are added to a first reactor maintained at 3000-3300° C., a second reactor maintained at 2000-2300° C. and a third reactor maintained at 1000-1200° C., respectively, and are gasified independently. The gasified silicon, gasified silicon dioxide and gasified magnesium are added to a mixing reactor at a weight ratio of 46.1:46.1:7.8 to prepare a mixed gas.

[0175] Specifically, the weight ratio of the vaporized silicon, the vaporized silicon dioxide, and the vaporized magnesium was measured using an Inductively Coupled Plasma Emission Spectrometer (ICP-OES, Optima 8300) manufactured by Perkin-Elmer.

[0176] The mixed gas was reacted and cooled by a cooling sheet maintained at 25° C., thereby preparing a primary silicon composite oxide. The primary silicon composite oxide was added to an air flow pulverizer and pulverized.

[0177] 50 g of the crushed primary silicon composite oxide was added to a reactor maintained at 900-1200° C. and maintained for 1 hour while injecting Ar gas and a carbon coating source at 1 L / min. Thus, a carbon coating was formed on the surface of the crushed primary silicon composite oxide, thereby preparing a silicon composite oxide. As the carbon coating source, ethylene was used.

[0178] The BET specific surface area of ​​the silicon composite oxide is 2.9 m 2 / g.

[0179] Specifically, the BET specific surface area is measured by the following method: using ASAP2420 (Micromeritics) equipment, using nitrogen as the adsorption gas, using helium as the carrier gas, and measuring by 5 predefined points of BET relative pressure based on the continuous flow method.

[0180] 2) Manufacturing of negative electrode

[0181] 5 wt % of the silicon composite oxide as a first negative electrode active material, 91.05 wt % of artificial graphite, 0.25 wt % of single-walled carbon nanotubes (SWCNTs) as a negative electrode conductive material, 2.4 wt % of styrene-butadiene rubber (SBR) as a binder, and 1.3 wt % of carboxymethyl cellulose (CMC) as a thickener were added to a pure water (deionized water) solvent and mixed to obtain a first negative electrode slurry.

[0182] 23 wt % of the silicon composite oxide as a second negative electrode active material, 74.85 wt % of artificial graphite, 0.25 wt % of SWCNT as a negative electrode conductive material, 0.6 wt % of styrene-butadiene rubber (SBR) as a binder, and 1.3 wt % of carboxymethyl cellulose (CMC) as a thickener were added to a pure water (deionized water) solvent and mixed to obtain a second negative electrode slurry.

[0183] The first negative electrode slurry and the second negative electrode slurry are coated on a Cu foil current collector, and then dried and rolled to form a first negative electrode active material layer and a second negative electrode active material layer.

[0184] Specifically, the first negative electrode slurry is coated on the Cu foil current collector, and the second negative electrode slurry is coated on the first negative electrode slurry. After that, the first negative electrode slurry and the second negative electrode slurry are dried together to form the first negative electrode active material layer and the second negative electrode active material layer.

[0185] 3) Manufacturing of positive electrode and secondary battery

[0186] LiNi as the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2, a mixture of carbon black and carbon nanotubes (CNT) as a positive electrode conductive material, and polyvinylidene fluoride (PVDF) as a positive electrode binder were mixed in distilled water at a weight ratio of 98.3:0.7:1 to prepare a positive electrode slurry. The positive electrode slurry was coated on an Al foil current collector and dried and rolled to manufacture a positive electrode.

[0187] A separator (polyethylene, 13 μm thick) was placed between the prepared positive electrode and negative electrode to form a battery, and the tab portion of the positive electrode and the tab portion of the negative electrode were welded, respectively.

[0188] The welded positive electrode / separator / negative electrode assembly is placed in a soft bag, and the portion with the pole ear is included in the sealing portion, and the three surfaces except the electrolyte injection surface are sealed. The electrolyte is injected through the electrolyte injection surface, and the electrolyte injection surface is also sealed, and then immersed for 12 hours to manufacture a secondary battery.

[0189] When preparing the electrolyte, 5 wt % of fluoroethylene carbonate (FEC), 0.5 wt % of propane sultone (PS) and 0.5 wt % of ethylene sulfate (ESA) were added to a 1 M LiPF6 solution using a mixed solvent of EC / EMC (25 / 75; volume ratio).

[0190] Preparation of carbon-coated silicon oxide

[0191] Silicon powder and silicon dioxide powder are added to a first reactor maintained at 3000-3300° C. and a second reactor maintained at 2000-2300° C., respectively, and are gasified independently. The gasified silicon and the gasified silicon dioxide are added to a mixing reactor at a weight ratio of 1:1 to prepare a mixed gas.

[0192] The mixed gas was reacted and cooled by a cooling sheet maintained at 25° C., thereby preparing primary silicon oxide. The primary silicon oxide was added to an air flow pulverizer for pulverization.

[0193] 50 g of the pulverized primary silicon oxide was added to a reactor maintained at 900-1200° C. and maintained for 1 hour while injecting Ar gas and a carbon coating source at 1 L / min to form a carbon coating on the surface of the pulverized primary silicon oxide, thereby preparing a silicon oxide coated with carbon. As the carbon coating source, ethylene was used.

[0194] Examples 2 to 8 and Comparative Examples 1 to 8

[0195] In the preparation of silicon composite oxide (C-Mg-SiO x ) or carbon-coated silicon oxide (C-SiO x ), the carbon coating source, the type and content of the active material contained in the first negative electrode active material layer, and the type and content of the active material contained in the second negative electrode active material layer are adjusted as shown in Table 1 below.

[0196] Examples 2 to 8 and Comparative Examples 1 to 8 were prepared by the same method as Example 1, except that, when preparing the silicon composite oxide, the weight ratio of vaporized silicon, vaporized silicon dioxide and vaporized magnesium added to the mixing reactor and the specific surface area of ​​the silicon composite oxide or the carbon-coated silicon oxide were adjusted as shown in Table 2 below.

[0197] [Table 1]

[0198]

[0199]

[0200] [Table 2]

[0201]

[0202] Experimental example

[0203] (1) XRD analysis - C-Mg-SiO x Measurement of the crystal size of the (220) plane

[0204] For the embodiments and comparative examples, the C-Mg-SiO x The crystal size of the (220) plane of (silicon composite oxide).

[0205] [Formula 1]

[0206]

[0207] In Formula 1, L 220 is the crystal size of the (220) plane (nm), K is the shape factor (0.8), λ is the X-ray wavelength (nm), β 220is the half maximum width (radian) of the peak of the (220) plane analyzed by XRD, and θ is the diffraction angle (radian).

[0208] In addition, specific XRD analysis equipment / conditions are shown in Table 3 below.

[0209] [Table 3]

[0210]

[0211] (2) Evaluation of initial capacity efficiency

[0212] The lithium secondary batteries manufactured according to the examples and comparative examples were charged in a chamber at 25° C. (CC-CV 1 / 3C 4.2V 0.05C CUT-OFF) and then measured for battery capacity (initial charge capacity), and then discharged (CC 1 / 3C 2.5V CUT-OFF) and then measured for battery capacity (initial discharge capacity).

[0213] The initial capacity efficiency was evaluated by converting the value obtained by dividing the measured initial discharge capacity by the measured initial charge capacity into a percentage (%).

[0214] (3) Normal temperature life (cycle) characteristics

[0215] The lithium secondary batteries manufactured according to the embodiments and comparative examples were subjected to 800 charge / discharge cycles at room temperature (25° C.). In each of the charge / discharge cycles, the batteries were charged at 1 / 3C 4.2V and 0.05C cutoff and then allowed to stand for 10 minutes, and discharged at 0.5C and 2.5V cutoff and then allowed to stand for 10 minutes.

[0216] The normal temperature life characteristics were evaluated by calculating, as a percentage, the ratio of the discharge capacity measured after performing the charge / discharge cycle 800 times to the discharge capacity measured after performing the charge / discharge cycle once.

[0217] The evaluation results are shown in Table 4 below.

[0218] [Table 4]

[0219]

[0220] As shown in Table 4, the silicon composite oxide used as the active material is a silicon composite oxide coated with carbon using ethylene or acetylene as a carbon source and has a BET specific surface area of ​​2.0-6.5 m 2 In the embodiment with a capacity of 1000 W / g, the initial capacity efficiency is above 81%.

[0221] In Example 2, in which the silicon composite oxide used as the active material was a silicon composite oxide coated with carbon using acetylene as a carbon source, the room temperature life characteristics and the initial capacity efficiency were slightly reduced.

[0222] In Examples 3 and 5 in which the content of the silicon composite oxide active material was reduced, the initial capacity efficiency was slightly reduced.

[0223] In Examples 4 and 6 in which the content of the silicon composite oxide active material was increased, the initial capacity efficiency was slightly reduced.

[0224] In Example 7 in which the BET specific surface area of ​​the silicon composite oxide was increased but the crystal size of the silicon composite oxide and the weight of magnesium were decreased, the initial capacity efficiency was increased but the normal temperature life characteristics were slightly decreased.

[0225] In Example 8 in which the BET specific surface area of ​​the silicon composite oxide was reduced but the crystal size of the silicon composite oxide and the weight of magnesium were increased, the room temperature life characteristics and the initial capacity efficiency were slightly reduced.

[0226] In the comparative example using silicon oxide containing no magnesium and coated with carbon as the active material, the room temperature life characteristics and the initial capacity efficiency were reduced.

[0227] The BET surface area exceeds 6.5 m 2 / g and in Comparative Example 5 in which the crystal size of the silicon composite oxide was reduced, the room temperature life characteristics and the initial capacity efficiency were deteriorated.

[0228] The BET specific surface area is less than 2.0 m 2 In Comparative Example 6 in which the crystal size of the silicon composite oxide was increased and the room temperature life characteristics and the initial capacity efficiency were reduced.

[0229] In Comparative Example 7, in which the silicon composite oxide used as the active material was a silicon composite oxide coated with carbon using methane as a carbon source, the initial capacity efficiency was low.

[0230] In Comparative Example 8 in which the silicon composite oxide used as the active material was carbon-coated using methane as a carbon source and the crystal size of the silicon composite oxide was increased, the room temperature life characteristics and the initial capacity efficiency were reduced.

Claims

1. A negative electrode for a secondary battery, comprising: Anode current collector; a first negative electrode active material layer, the first negative electrode active material layer being disposed on at least one side of the negative electrode current collector and comprising a first negative electrode active material comprising a first silicon composite oxide; and a second negative electrode active material layer, the second negative electrode active material layer being provided on the first negative electrode active material layer and comprising a second negative electrode active material containing a second silicon composite oxide, wherein the first silicon composite oxide and the second silicon composite oxide each contain a metal, The BET specific surface areas of the first silicon composite oxide and the second silicon composite oxide are 2.0-6.5 m 2 / g.

2. The negative electrode for a secondary battery according to claim 1, wherein The metal comprises magnesium.

3. The negative electrode for a secondary battery according to claim 2, wherein: The first silicon composite oxide and the second silicon composite oxide each have a carbon coating formed on a surface thereof, and include SiO doped with magnesium. x , where 0 <x<2。 4. The negative electrode for a secondary battery according to claim 2, wherein The first silicon composite oxide and the second silicon composite oxide each contain 5.0 to 10.0 wt % of magnesium.

5. The negative electrode for a secondary battery according to claim 1, wherein In the total weight of the first negative electrode active material layer and the second negative electrode active material layer, the sum of the weight of the first silicon composite oxide and the second silicon composite oxide is 10-20 wt %.

6. The negative electrode for a secondary battery according to claim 5, wherein A content of the first silicon composite oxide contained in the first negative electrode active material layer on a weight basis is smaller than a content of the second silicon composite oxide contained in the second negative electrode active material layer on a weight basis.

7. The negative electrode for a secondary battery according to claim 6, wherein: The content of the first silicon composite oxide is 2-10 wt % in the total weight of the first negative electrode active material layer.

8. The negative electrode for a secondary battery according to claim 6, wherein The content of the second silicon composite oxide is 18-30 wt % in the total weight of the second negative electrode active material layer.

9. The negative electrode for a secondary battery according to claim 1, wherein The crystal size of the (220) plane of each of the first silicon composite oxide and the second silicon composite oxide defined by the following formula 1 is 3.5-10 nm: [Formula 1] In formula 1, L 220 is the crystal size of the (220) plane in nm, K is the shape factor, λ is the X-ray wavelength in nm, β 220 is the half maximum width of the peak of the (220) plane analyzed by XRD, in radians, and θ is the diffraction angle, in radians.

10. The negative electrode for a secondary battery according to claim 1, wherein The BET specific surface areas of the first silicon composite oxide and the second silicon composite oxide are 2.5-6.0 m 2 / g.

11. A lithium secondary battery comprising: The negative electrode for a secondary battery according to claim 1; as well as A positive electrode is arranged opposite to the negative electrode.

12. A method for preparing a silicon composite oxide for negative electrode active material, comprising the following steps: reacting a mixed gas of silicon (Si), silicon dioxide (SiO2) and a metal to form a primary silicon composite oxide; as well as A carbon coating is formed on the surface of the primary silicon composite oxide using a carbon source having a pyrolysis temperature of 500-700°C.

13. The method for preparing a silicon composite oxide for negative electrode active material according to claim 12, wherein: The metal comprises magnesium.

14. The method for preparing a silicon composite oxide for negative electrode active material according to claim 12, wherein: The carbon source comprises at least one of ethylene and acetylene.